Development of accurate dose evaluation technique of X-ray inspection for quality assurance of semiconductor with Monte Carlo simulation. (December 2019) - Park, Hyojun; Choi, Hyun Joon; Rhew, Keunho; Lim, Heonsang; Lee, Hyunyoung; Jang, Iloh; Min, Chul Hee
Abstract: Since higher dose delivered to a semiconductor leads to more functional loss to the device, accurate dose evaluation of the semiconductor is very important to reduce the defect rate during x-ray inspection. The aim of this study is to develop the technique to accurately evaluate the absorbed dose to the semiconductor using the Monte Carlo method. The x-ray radiographic system was modeled based on the Geant4 Monte Carlo tool-kit. The Monte Carlo commissioning was performed by comparing the energy spectrum between the simulation and measurement. The dose evaluation technique for the semiconductor was developed, and the dose delivered to the semiconductor device was evaluated according to various x-ray energies. The energy spectrum of the x-ray beam simulated with Geant4 was validated with the experiment using the CdTe detector for various x-ray beams. The accurate dose to the semiconductor component was assessed according to various x-ray energies. The x-rays of 25 keV energy delivered the highest dose to the silicon die, while the 67.5 keV showed the minimum dose to the die. It was observed that the higher energy over about 70 keV also increased the dose with the scattered photons produced in the solder ball and circuit board. The technique to accurately determine the absorbed dose in the semiconductor was suggested and the x-ray energy deliver the high dose to the semiconductor die was assessed. These results could be fundamentally used to reduce the dose in semiconductor and defect rate in x-ray inspection. Highlights: X-ray radiography system was modeled based on Geant4 Monte Carlo tool-kits. The energy spectrum of the radiography system was measured. Radiographic image of the semiconductor device was obtained with the Geant4-based x-ray radiography system. Absorbed dose to the main components inside the semiconductor device was estimated according to the energy of x-rays.